143 CLINICAL VIGNETTE: COMMON VACCINES, UNCOMMON PROBLEM: HEMOLYTIC ANEMIA FOLLOWING ROUTINE VACCINATION. Issue 1 (1st January 2007) - Dill, C. P.; Moss, C. N.; Kalwinski, D. K.; Smalligan, R. D.
Abstract : Objective: To remind pediatricians of a rare but serious complication that can occur following routine vaccination. Case: A previously healthy 12-month-old girl presented with an 18-day history of increasing irritability, somnolence, and fever that began shortly after receiving her third dose of pneumococcal conjugate vaccine and her first dose of varicella vaccine. PMH: No previous vaccine reactions, surgeries, hospitalizations, or serious illnesses. PE: T36.5C, P154, R26, BP 126/59. Pale but playful girl with clear rhinorrea, normal tympanic membranes, clear lungs, 2/6 systolic ejection murmur, no organomegaly, and no edema. Labs: WBC 10.3, HGB 5.8, retics 4.3 corrected, Tbili 1.5, normal transaminases, direct Coombs' 3+ with warm autoantibodies present. The patient was admitted and treated with IV steroids, IVIG, and one transfusion. Eleven days later she was discharged with a HGB of 9.7. Serology 3 months later revealed adequate IgG antibodies to varicella and a negative direct Coombs' test. She was tapered off steroids over 4 months, and there have been no relapses of hemolytic anemia in over 3 years despite subsequent vaccines. Discussion: This case of autoimmune hemolytic anemia (AIHA) illustrates an extremely uncommon complication of routine vaccination in a healthy child. Although cases of AIHA have been reported after DTP, oral polio, hepatitis B, measles, H. influenza, smallpox, and other vaccines, no reports could be found implicating the varicella or pneumoccocal vaccines. This child had the most common form of AIHA, which is characterized by warm IgG autoantibodies, usually formed in response to infections, autoimmune disorders, immunodeficiency syndromes, malignancies, or medications. Mortality from warm AIHA in the pediatric age group ranges from 9 to 29% and is usually due to severe anemia or hemorrhage from associated thrombocytopenia. Corticosteroid therapy is first-line treatment followed by immunosuppressive drugs and splenectomy in refractory cases. Other treatment options include IVIG, plasmapheresis, and immunomodulary agents. As the number of recommended childhood vaccines increase, pediatricians should be aware of the possibility of rare but important complications such as AIHA.